2015
DOI: 10.1002/chem.201501580
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Aspects of Aryl–Halide Oxidative Addition, Coordination Chemistry, and Ring‐Walking by Palladium

Abstract: This contribution describes the reactivity of a zero-valent palladium phosphine complex with substrates that contain both an aryl halide moiety and an unsaturated carbon-carbon bond. Although η(2) -coordination of the metal center to a C=C or C≡C unit is kinetically favored, aryl halide bond activation is favored thermodynamically. These quantitative transformations proceed under mild reaction conditions in solution or in the solid state. Kinetic measurements indicate that formation of η(2) -coordination compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 132 publications
2
6
0
Order By: Relevance
“…The values of stabilization energy of complexation of stilbene, tolan, and azobenzene with t-Bu 3 PPd were −27.9, −25.6, and −20.8 kcal/mol, respectively ( Figures S3-S5). These results support our interpretation, although calculations for model PdPH 3 systems with ethylene and acetylene indicated that the Pd-C bonds are stronger in the acetylene complex than in the ethylene complex [16,17].…”
Section: Suzuki-miyaura Coupling Reaction Of 1 Withsupporting
confidence: 88%
“…The values of stabilization energy of complexation of stilbene, tolan, and azobenzene with t-Bu 3 PPd were −27.9, −25.6, and −20.8 kcal/mol, respectively ( Figures S3-S5). These results support our interpretation, although calculations for model PdPH 3 systems with ethylene and acetylene indicated that the Pd-C bonds are stronger in the acetylene complex than in the ethylene complex [16,17].…”
Section: Suzuki-miyaura Coupling Reaction Of 1 Withsupporting
confidence: 88%
“…This selectivity was such that the normal order of reactivity of aryl halides (I > Br > Cl) could be overturned, and was attributed to a 'ring-walking' process where the nickel moves from the initial site of coordination across a π-system to the aryl halide. [46][47][48][49][50][51] This proposal was supported by DFT calculations.…”
Section: Reactions With Aryl Halidesmentioning
confidence: 59%
“…Alkoxopalladium G undergoes β-carbon elimination with the release of acetone, providing the arylpalladium H followed by reductive elimination to yield aryl bromide 8 and regenerate the initial palladium species. Subsequently, the smooth oxidative addition of 8 likely proceeds through a ring-walking pathway , to generate arylpalladium species I , which undergoes the 6- endo - trig cyclization to furnish benzylpalladium intermediate J . Finally, β-hydrogen elimination from J releases the desired phenanthrene 3a with the initial palladium catalyst regenerated.…”
Section: Resultsmentioning
confidence: 99%